CRESCIMENTO E PRODUTIVIDADE DE GENÓTIPOS DE BATATA SOB DIFERENTES DOSES DE NPK - SANTOS, KELI CRISTINA DOS (2015)
The objective of this study was to estimate the growth and yield of distinct potato genotypes, cultivated with different doses of NPK fertilizer 4-14-8 in Guarapuava-PR region. Therefore, two experiments were conducted, the first one in a commercial potato crop, manage by the producer in the agricultural year of 2013/14 and the second one conducted in the agricultural year of 2014/15, at the experimental area of CEDETEG Campus of West Central State University. The experimental design was subdivided plots with split plot design, and in the plots were distributed the 0, 2, 4 and 6 t ha-1 doses of NPK fertilizer 4-14-8 and in the subplots were distributed in the first growing season (2013/14) BRS Camila and Agata cultivars and C0205 clone and in the second growing season (2014/15) only BRS Camila and Agata cultivars. Were evaluated morphological parameters, yield data, and the greening of tubers after harvest. The evaluations were performed at 25 and 45 days after emergence (DAE) for the first growing season and at 28 and 48 DAE for the second growing season and after physiological maturity (harvest) in both years. It was observed differences among genotypes, and the C0205 clone produced higher plants more number of nodes, number of secondary stems, IAF and commercial tuber mass in the growing season of 2013/14. The Agate and 'BRS Camila' cultivars produced plants with similar morphological characteristics and -yield potential, but 'BRS Camila' produced in the first growing season higher amount of total tubers with less fertilizer than Agata. On the other hand, the second crop year tubers of BRS Camila greening more easily than' Agata '. The potato plants were influenced by the fertilizer doses tested for all morphological characteristics in both growing seasons. For yield the response were for commercial tubers mass and percentage of dry mass in both years and growing season for 2014/15. Thus it is possible to concluded that C0205 clone despite being highly productive and showed the best results in the first growing season, it is not commercially viable due to produce tubers with low quality, while 'Agate' has high productivity and BRS Camila 'comes to the market to compete with good results with 'Agata'. The results reflect the importance of research to adjust the crop management to obtain the best productive performance for each genotype.